Procrustes analysis of vocabulary flow graphs - Teraza, Niomi T. (2010)
This study was conducted to determine the optional scan length in the vocabulary flor graphs. This was done through the comparison of the vocabulary flow graphs using different scan lengths though Procrustes Analysis in three textual data. Four scan lengths were used, namely: 100, 300, 500 and 1000. Using Procrustes Analysis, the vocabulary flow graphs formed from each scan lengths in each textual data were compared. Dissimilarity measures were obtained from the comparison of different scan lengths of the vocabulary flow graphs. Procrustes Statistic followed in order to test if the obtained dissimilarity measures were significant in each of the three-textual data. The end result is that all the dissimilarity measures from the comparison of scan lengths were all significant. This study had an implication in Guillermo?s translation analysis (2009) wherein he had only chosen scan length 300 as the optimal scan length among the four scan lengths. But based on the results of this study, it is still reasonable to believe that Guillermo had chosen scan length from 100, 300, 500 and 1000 were optimal values of scan lengths through the test for significance of the obtained dissimilarity measures in Procrustes statistics